Modified Ag/TiO2 systems: Promising catalysts for liquid-phase oxidation of alcohols; Fuel; Vol. 234 - Kolobova E. N. Ekaterina Nikolaevna; Kotolevich Yu. Yulia; Pakrieva E. G. Ekaterina Germanovna; Mamontov G. Grigory; Farнas M. H. Mario; Corberan V. C. Vicente Cortes; Bogdanchikova N. Nina; Hemming J. Jarl; Smeds A. I. Annika; Maki-Arvela P. Paivi; Murzin D. Yu. Dmitry; Pestryakov A. N. Aleksey Nikolaevich (2018, 2018)
Title screen